Modulation of insulin degrading enzyme activity and liver cell proliferation - Pivovarova-Ramich, Olga; Sticht, Carsten; Gretz, Norbert; Dooley, Steven (Cell cycle, 2015)
Diabetes mellitus type 2 (T2DM), insulin therapy, and hyperinsulinemia are independent risk factors of liver cancer. Recently, the use of a novel inhibitor of insulin degrading enzyme (IDE) was proposed as a new therapeutic strategy in T2DM. However, IDE inhibition might stimulate liver cell proliferation via increased intracellular insulin concentration. The aim of this study was to characterize effects of inhibition of IDE activity in HepG2 hepatoma cells and to analyze liver specific expression of IDE in subjects with T2DM. HepG2 cells were treated with 10 nM insulin for 24 h with or without inhibition of IDE activity using IDE RNAi, and cell transcriptome and proliferation rate were analyzed. Human liver samples (n = 22) were used for the gene expression profiling by microarrays. In HepG2 cells, IDE knockdown changed expression of genes involved in cell cycle and apoptosis pathways. Proliferation rate was lower in IDE knockdown cells than in controls. Microarray analysis revealed the decrease of hepatic IDE expression in subjects with T2DM accompanied by the downregulation of the p53-dependent genes FAS and CCNG2, but not by the upregulation of proliferation markers MKI67, MCM2 and PCNA. Similar results were found in the liver microarray dataset from GEO Profiles database. In conclusion, IDE expression is decreased in liver of subjects with T2DM which is accompanied by the dysregulation of p53 pathway. Prolonged use of IDE inhibitors for T2DM treatment should be carefully tested in animal studies regarding its potential effect on hepatic tumorigenesis.